An improved method for microbiological testing of paper-based laminates used in food packaging. (April 2015) - Feichtinger, Marlies; Zitz, Ulrike; Fric, Helmut; Kneifel, Wolfgang; Domig, Konrad J.
Abstract: Food packaging materials fundamentally contribute to food quality and safety, as they protect the packaged food against external influences. In this context, the determination of the hygiene status of the packaging material is of great importance. However, European legislation neither sets any microbiological criteria nor provides any approved standard for the microbiological testing of food packaging materials. Nevertheless, reliable routine control is essential for guaranteeing high hygienic quality of packagings. With the aim to achieve a maximum recovery rate at low contamination levels, an improved experimental design was developed for the enumeration of the total colony count, yeasts and molds and Enterobacteriaceae on the surface of roll stock packaging materials. For this purpose, two different types of paper laminates were selected and exemplarily used as objects of investigation. Moreover, the performance of different growth media was compared for each microbiological parameter. This approach was followed by method validation using a selection of quantitative reference materials of representative microorganisms, including resistant forms of microbes such as bacterial endospores and fungal spores. Highlights: There is no official method for microbiological control of food contact materials. The only available guideline is not suitable for the assessment of paper-laminates. A routine method was developed and validated for its efficiency. The new method is simple, low in costs and produces quantitative results.